Incidence and Outcomes of Endophthalmitis Associated Hospitalizations in Children Aged ≤ 20 Years: A Population-Based Cohort Study. (4th October 2017) - Edwards, Brett; Lekhi, Vikram; Parkins, Michael; Somayaji, Ranjani
Abstract: Background: Endophthalmitis is a rare but sight-threatening condition in children, and is most commonly attributable to surgery, endogenous spread of infection, and trauma. Few population-based studies have examined the epidemiology and outcomes of neonatal and pediatric endophthalmitis. Methods: Using the 2012 Kids' Inpatient Database, a stratified random sample of pediatric (≤ 20 years) discharges from community and non-rehabilitation hospitals in the US, we conducted a cohort study to examine the incidence and outcomes of endophthalmitis. The ICD9-CM search codes included 360.0*, 360.13 and 360.19 for endophthalmitis. Our primary outcome was the incidence of endophthalmitis hospitalizations in children. Demographics of sex, age, and race were described. Outcomes of death, length of stay (LOS in days), and total costs were described and compared (with weighting) between neonatal (< 4 weeks) and pediatric cases. Results: A total of 344 hospitalizations (58.1% male, median age 0 years (IQR 0–10 years) occurred for endophthalmitis corresponding to a national total of 478 cases at an incidence rate of 7.2 cases per 100, 000 persons. Of these, 50.3% were neonatal endophthalmitis cases. Endophthalmitis was most common in the Caucasian (51.1%), Hispanic (21.9%) and Black (16.6%) races. The overall mortality was not significantly different between pediatric and neonatal cases (OR 1.46, 95% CI 0.24 – 8.90). For LOS, neonatal patients with endophthalmitis had a significantly greater LOS by 14.30 days (95% CI 7.97–19.52, P <0.001) compared with pediatric patients. Neonatal cases also had a significantly greater associated cost compared with pediatric cases (difference $77, 626, 95% CI $16, 703–$138, 500, P  = 0.01). Conclusion: Our population-based study demonstrated that neonatal endophthalmitis was associated with similar incidence rates and mortality, but greater LOS and health care costs compared with pediatric endophthalmitis. Disclosures: All authors: No reported disclosures.